(untitled) (St. Louis, 1998)
Textbook on the essentials of case management for third-party payers and insurance carriers. Includes guidelines on how to set up and operate a case management program. Softcover. DNLM: Managed Care Programs--organization & administration.
Keywords: Managed care plans (Medical care),Medical care,Health insurance claims,Bảo hiểm y tế,Chăm sóc sức khỏe; Management,Utilization review